PENATAAN PERATURAN PERUNDANG-UNDANGAN JAMINAN SOSIAL KETENAGAKERJAAN PADA ERA SOCIETY 5.0 - Suirwan, Suirwan; I Dewa Ayu Widyani; Yuni Artha Manalu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The formulation of the problem in this thesis are 1) how is the implementation of the employment social security program according to statutory provisions, and 2) how is the arrangement of employment social security legislation in the Society 5.0 era as a result of the issuance of the Job Creation Law and the P2SK Law. This research is normative legal research with a statutory and conceptual approach. From the results of this study it can be concluded that the implementation of the employment social security program regulated in the SJSN Law and the BPJS Law is the basis for carrying out the mandate of the 1945 Constitution, especially Article 28H Paragraph (3) and Article 34 Paragraph (2), which shows that the state is committed to creating and promote the general welfare. In the concept of a rule of law, especially a formal rule of law state, state intervention in the pursuit of public welfare is realized by the effective and efficient implementation of social security for all citizens, although there are still deficiencies in its implementation as per the results of various studies and evaluations by the competent authorities. For legal certainty, it is necessary to structuring employment social security laws and regulations which can be carried out by 1) Structuring the types, hierarchy and content material of laws and regulations related to the mandate of the P2SK Law and the Job Creation Law related to the JHT program, harmonization of the Pension Program, and cut-loss arrangements as well reduction in investment value, as well as the implementation of the Constitutional Court’s decision regarding program transfer and program implementation by BPJS and 2) Structuring the substance of laws and regulations related to evaluating retirement age, adjusting the amount of pension security contributions, and optimizing regulations for implementing Presidential Instruction Number 2 of 2021.